A tactical retreat? Conceptualising the dynamics of European grocery retail divestment from East Asia. Issue 1 (February 2019) - Burt, Steve; Coe, Neil M.; Davies, Keri
Highlights: Longitudinal study of European retail divestment in East Asia over 30 years. Three distinct phases of international retail divestment in East Asia can be identified. Different combinations of divestment pressures and outcome rationales emerge in each phase. Similar underlying pressures present but nature and importance varies over time. Priorities vary over time – local (host) market, regional to global firm centric considerations. Abstract: The internationalisation of the firm is a highly dynamic process, in which periods of investment and expansion intermingle with periods of divestment and retrenchment. Academic research to date has focused on identifying the reasons for and the processes of divestment. Empirical studies either evidence generic pressures or provide case studies of specific incidents. There few longitudinal studies of international divestment, consequently the dynamic interactions between host market, home market and firm level factors, and how the institutional context changes over time is underplayed. This paper seeks to rectify this gap in our understanding. We explore the rationale and evolving dynamics of European grocery retail divestment in East Asia over a thirty year period. Taking an inductive approach and drawing on analysis of contemporary narratives drawn from company documentation, trade journals, newsfeeds and market reports, three phases can be identified characterised by specific factors and combinations of factors which intersect to provide the key pressures and stimuli for divestment. We conclude that at different time periods, different internal and external contextual influences manifest themselves through different priorities within the firm's strategy – marked by a switch from local (host) market, to regional, to global firm-centric considerations. Longitudinal analyses allow a greater recognition of this dynamic interplay of factors, and the changes in these relationships, and provides a more nuanced understanding of the international divestment process.